PENGEMBANGAN SOFT SKILLS REMAJA MASJID MELALUI KEGIATAN PELATIHAN KEPEMIMPINAN DAN KOMUNIKASI BAGI REMAJA MASJID DI DESA KARYAMEKAR, GARUT, JAWA BARAT - Irman Ramdhan Fauzi; Denny Aditya Dwiwarman; Halimatun Sadiyah; Enden Suryati; Dariyanto, Dariyanto (JURNAL ABDIMAS PLJ, 2025)
This community service activity aims to improve the leadership capacity and communication skills of mosque youth in Karyamekar Village, Garut Regency, West Java. As the younger generation with a strategic role in social and religious development, mosque youth are expected to emerge as communicative, inspiring, and articulate agents of change. However, this significant potential has not been fully supported by adequate training in leadership and communication. Through this training, the implementing team will provide materials and direct mentoring to the participants, who are members of the village's mosque youth. The activity is designed as a two-day participatory training that encompasses theory and practice, using methods such as interactive lectures, group discussions, role-plays, public speaking simulations, and leadership case studies. The core materials in this training include: leadership fundamentals, leadership types, effective communication techniques, public speaking skills, and strategies for managing religious organizations or activities. Furthermore, the training will highlight ethical values, social responsibility, and the role of youth in strengthening Islamic values ​​in society. It is hoped that after participating in this program, participants will significantly improve their self-confidence, leadership skills, and communication skills, which can be applied to organizational life, mosque activities, and community social life. This program is also expected to serve as a starting point for developing young cadres ready to become future leaders, both within the mosque and in the village community at large.